The effects of listing status on a firm’s lease accounting: Evidence from South Korea - Younghee Park; Kyunga Na (Gadjah Mada International Journal of Business, 2017)
This study examines how the listing status affects a firm’s choice of lease accounting, using 7,023 firm-year observations that record either an operating or a capital lease from 2001 to 2013 in Korea. We find that unlisted firms are more likely to opt for operating leases, and to have a higher ratio of operating leases than listed firms are. These results indicate that unlisted firms tend to prefer operating leases which can be used as a tool to avoid increasing debt levels and to benefit from off-balance sheet financing (or unrecorded liabilities), compared to listed firms. This study contributes to the current accounting literature as it is the first to provide empirical evidence regarding the impact of the listing status on a firm’s lease accounting.